Experimental study of the effect of adding bioethanol to RON 90 gasoline on exhaust gas emissions of a four-stroke motor vehicle - Hadi Sutanto; Christefa Hendy Setianto (Jurnal Teknika, 2021)
The use of biofuels in the world is increasing due to their economic prices and an energy crisis. Bioethanol is an alternative renewable fuel suitable for use in internal combustion engines. When compared to the octane number of gasoline, this fuel has a relatively high octane number. Another major property is that bioethanol can reduce motor vehicle emissions when compared to fossil fuels. This study aimed to determine the number of exhaust emissions with fuel that uses a mixture of pertalite RON 90 gasoline and bioethanol. The test method uses a loaded engine with three rpm variations, namely 1200, 6000, and 9000 rpm, with exhaust emission measurement parameters consisting of CO2, CO, HC, and NOx. The test used four kinds of bioethanol mixtures, namely bioethanol 5% (E5), bioethanol 10% (E10), bioethanol 15% (E15), and bioethanol 20% (E20), in addition to pure gasoline RON 90 (pertalite). Measurement of exhaust emissions is carried out using an exhaust gas analyzer. The test results show that using a mixture of bioethanol as fuel does not reduce the total amount of exhaust emissions. The proportion of CO2 tends to grow as the bioethanol mixture increases, and vice versa for the percentage of CO. Meanwhile, the proportion of HC reduced as the bioethanol mixture rose, whereas the percentage of NOx increased. Penggunaan bahan bakar nabati di dunia semakin bertambah disebabkan oleh harga ekonomisnya dan adanya krisis energi. Bioetanol sebagai bahan bakar alternatif yang bersifat terbarukan sesuai untuk digunakan pada mesin pembakaran dalam. Bahan bakar ini memiliki angka oktan yang cukup tinggi jika dibandingkan dengan angka oktan bensin. Sifat utama yang lain yaitu bioetanol dapat mengurangi emisi kendaraan bermotor jika dibandingkan dengan bahan bakar fosil. Tujuan dari penelitian ini untuk mengetahui besar emisi gas buang dengan bahan bakar yang menggunakan campuran bensin jenis pertalite RON 90 dan bioetanol. Metode pengujian menggunakan mesin terbebani dengan tiga macam variasi rpm yaitu 1200, 6000 dan 9000 rpm dengan parameter pengukuran emisi gas buang terdiri dari CO2, CO, HC dan NOx. Pengujian menggunakan empat macam campuran bioetanol, yaitu bioetanol 5% (E5), bioetanol 10% (E10), bioetanol 15% (E15) dan bioetanol 20% (E20), selain bensin murni RON 90 (pertalite). Pengukuran emisi gas buang dilakukan dengan menggunakan exhaust gas analyzer. Hasil pengujian menunjukkan bahwa penggunaan campuran bioetanol sebagai bahan bakar tidak mengurangi seluruh jumlah emisi gas buang. Persentase CO2 cenderung naik terhadap kenaikan campuran bioetanol dan sebaliknya pada persentase CO. Sedangkan persentase HC menurun dengan naiknya campuran bioetanol dan sebaliknya persentase NOx meningkat dengan campuran bioetanol pada bensin.